2018
DOI: 10.1093/eurheartj/ehy802
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of reduced-dose non-vitamin K antagonist oral anticoagulants in patients with atrial fibrillation: a meta-analysis of randomized controlled trials

Abstract: Aims Non-vitamin K antagonist oral anticoagulants (NOACs) require dose reductions according to patient or clinical factors for patients with atrial fibrillation (AF). In this meta-analysis, we aimed to assess outcomes with reduced-dose NOACs when given as pre-specified in pivotal trials. Methods and results Aggregated data abstracted from Phase III trials comparing NOACs with warfarin in patients with AF were assessed by trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 36 publications
3
38
1
1
Order By: Relevance
“…Indeed, inappropriate low dose regimen is associated with lower DOAC levels [77] and with increased thromboembolic risk [78]. AF patients eligible for DOAC reduced-doses represent a common and troublesome scenario in clinical practice, as it has been recently demonstrated that these patients are at increased risk both of thromboembolic and hemorrhagic complications [72,79,80]. However, in phase III DOAC trials patients who were appropriately dose-adjusted, had a better benefit/harm ratio compared to warfarin [79].…”
Section: Selection and Dosing Of Doacmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, inappropriate low dose regimen is associated with lower DOAC levels [77] and with increased thromboembolic risk [78]. AF patients eligible for DOAC reduced-doses represent a common and troublesome scenario in clinical practice, as it has been recently demonstrated that these patients are at increased risk both of thromboembolic and hemorrhagic complications [72,79,80]. However, in phase III DOAC trials patients who were appropriately dose-adjusted, had a better benefit/harm ratio compared to warfarin [79].…”
Section: Selection and Dosing Of Doacmentioning
confidence: 99%
“…AF patients eligible for DOAC reduced-doses represent a common and troublesome scenario in clinical practice, as it has been recently demonstrated that these patients are at increased risk both of thromboembolic and hemorrhagic complications [72,79,80]. However, in phase III DOAC trials patients who were appropriately dose-adjusted, had a better benefit/harm ratio compared to warfarin [79]. A post-hoc analysis of the ARISTOTLE trial demonstrated that patients fulfilling just one of the pre-specified criteria for apixaban dose-reduction, and appropriately treated with the standard dose, had similar rates of major bleedings compared to those receiving full-dose apixaban in the absence of any dose-reduction criteria [81].…”
Section: Selection and Dosing Of Doacmentioning
confidence: 99%
“…Oral anticoagulation (OAC) with vitamin K antagonists (VKA) or direct oral anticoagulants (DOAC) is the standard of care for primary and secondary prevention in patients with nonvalvular AF [1,5]. Compared to VKA, DOACs provide a superior benefit-risk profile [6][7][8][9][10], mainly driven by a lower risk of intracranial bleeding complications [11,12]. The dose regimens of the three currently available oral Xa inhibitors warrant adjustment to lower daily doses in certain clinical conditions, while the criteria for the reduction were defined substance-specifically and include age, different degrees of chronic renal failure, body weight and the risk of drug interactions [1,13].…”
Section: Introductionmentioning
confidence: 99%
“…However, data from real word cohorts reported a significant proportion of patients to be using an inappropriate low dose of these substances. This off-label use was associated with an elevated risk of hospitalization and death [11,14]. In the present study we explored the rate of Factor Xa inhibitor underdosing among patients with acute cerebral ischemia, its effects on Xa inhibitor plasma levels, stroke severity as well as the functional outcome after 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…43) In a recent meta-analysis, patients who received a reduced dose of NOAC in the pivotal RCTs showed comparable efficacy and superior safety compared with warfarin, and these results were consistent with the relative benefit observed in the comparison between full dose NOAC and warfarin. 44) Namely, although patients eligible for a reduced dose of NOACs generally had an elevated risk of thromboembolic and hemorrhagic complications, appropriately doseadjusted NOACs showed a consistent benefit-harm profile compared with warfarin.…”
Section: Clinical Impact Of Off-label Dosing Of Noacsmentioning
confidence: 97%